1981
DOI: 10.1007/bf00422469
|View full text |Cite
|
Sign up to set email alerts
|

Frequency analysis of surface EMG to evaluation of muscle fatigue

Abstract: A theory concerning the spectral density of surface electromyogram (EMG) in isometric contraction is described and herein, a conduction velocity measure, which was derived from a surface EMG model, is suggested. In order to confirm the validity of this measure, the spectral modification with respect to muscle fatigue is studied experimentally. The EMG signals were obtained from the biceps brachii and the rectus femoris in four subjects. The spectral modification shifted to a lower frequency as fatigue develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…1; Basmajian and DeLuca 1985, for references). The shift in EMG spectral density function towards lower frequency components has been suggested to be associated with a reduction in muscle conduction velocity (Mortimer et al 1970;Sadoyama and Miyano 1981;Stulen and DeLuca 1981;Arendt-Nielsen and Mills 1985). As further support for this theory, a linear relationship between the mean frequency and the conduction velocity during sustained contractions has been demonstrated (Naeije and Zorn 1982;Sadoyama et al 1983;Eberstein and Beattie 1985).…”
Section: Discussionmentioning
confidence: 82%
“…1; Basmajian and DeLuca 1985, for references). The shift in EMG spectral density function towards lower frequency components has been suggested to be associated with a reduction in muscle conduction velocity (Mortimer et al 1970;Sadoyama and Miyano 1981;Stulen and DeLuca 1981;Arendt-Nielsen and Mills 1985). As further support for this theory, a linear relationship between the mean frequency and the conduction velocity during sustained contractions has been demonstrated (Naeije and Zorn 1982;Sadoyama et al 1983;Eberstein and Beattie 1985).…”
Section: Discussionmentioning
confidence: 82%
“…PSD has also been reported to decrease with muscle fatigue [10]. sEMG amplitude is known to increase with muscle fatigue, and this is thought to result from an increase of motor units and impulse firing frequency, as well as synchronization of firing activity [11]. Although low-frequency components, PSD, and V p-p were found to contribute to the easiness of deglutition in our present study, the easiness of deglutition was only found to be significantly correlated with PSD Table 3: Mean scores for the easiness of deglutition (mean ± SD) was assessed by scoring in a 9-point scale (-4 to 4), muscle activity, Vp-p; highest peak voltage, lowfrequency component, high-frequency component, PSD: power spectral density (mean ± SE) for each test data sample.…”
Section: Discussionmentioning
confidence: 99%
“…In general, decreased entropy is associated with increased fatigue that could be associated with increased synchronization of motor unit [32]. All in all, the advanced biofeedback resulted in changes of irregularity in the pattern of muscle activation.…”
Section: Effects Of Advanced Biofeedbackmentioning
confidence: 93%